2019
DOI: 10.21608/zumj.2019.16429.1468
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Collagen Cross Linking With Photo-Activated Chromophore for keratitis (PACK-CXL) As AdjunctiveTherapy for Infectious Keratitis

Abstract: Background : The aim of this work is to evaluate efficacy and safety of corneal collagen cross linking as adjunctive therapy for treating infectious keratitis. Methods: This is a randomized prospective controled clinical trial. Seventy eight (78) eyes with clinically suspected infectious keratitis were enrolled in this study. The range of age of the enrolled patients was more than or equal to18 years. They were randomly classified into two groups each of 39 eyes, Group A(control group): received topical approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It was noted that a higher proportion of patients in the group receiving combination treatment of antibiotics with PACK-CXL experienced complete resolution of ulcers (97.4 vs 76.9%, p-value<0.001). Additionally, the mean resolution period was shorter in patients treated with PACK-CXL (7.02 ± 2 weeks vs 10.87 ± 3.28 weeks, p-value 0.002) (Tawfeek et al, 2020). Knyazer and colleagues have reported that additional PACK-CXL significantly reduces time to epithelial healing in ulcers up to 4 mm in size when using accelerated PACK-CXL and standardfluence of 5.4 J/cm 2 (Knyazer et al, 2020).…”
Section: Bacterial Keratitismentioning
confidence: 97%
See 1 more Smart Citation
“…It was noted that a higher proportion of patients in the group receiving combination treatment of antibiotics with PACK-CXL experienced complete resolution of ulcers (97.4 vs 76.9%, p-value<0.001). Additionally, the mean resolution period was shorter in patients treated with PACK-CXL (7.02 ± 2 weeks vs 10.87 ± 3.28 weeks, p-value 0.002) (Tawfeek et al, 2020). Knyazer and colleagues have reported that additional PACK-CXL significantly reduces time to epithelial healing in ulcers up to 4 mm in size when using accelerated PACK-CXL and standardfluence of 5.4 J/cm 2 (Knyazer et al, 2020).…”
Section: Bacterial Keratitismentioning
confidence: 97%
“…It was noted that a higher proportion of patients in the group receiving combination treatment of antibiotics with PACK-CXL experienced complete resolution of ulcers (97.4 vs 76.9%, p -value<0.001). Additionally, the mean resolution period was shorter in patients treated with PACK-CXL (7.02 ± 2 weeks vs 10.87 ± 3.28 weeks, p -value = 0.002) ( Tawfeek et al, 2020 ).…”
Section: Anti-infective Application Of Riboflavin and Ultraviolet-a For The Treatment Of Infective Keratitis (Pack-cxl)mentioning
confidence: 99%